The Effect of Liquidity and Leverage on Financial Distress in Textile and Garment Sector Companies on the Indonesia Stock Exchange (IDX) for the 2021-2024 Period - Nadia Fuji Lestari; Adinda Fitra Amalia; Salma Fadhlatun Najwa (Green Publisher Indonesia, 2026)
This study aims to analyze the influence of liquidity and leverage on financial distress in textile and garment sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The research uses a quantitative approach with secondary data in the form of annual financial statements. Samples are determined through purposive sampling techniques. Liquidity is proxied by the current ratio, leverage by the debt to asset ratio, while financial distress is measured using earnings per share (EPS). Data analysis was carried out using panel data regression, with model selection through Chow, Hausman, and Lagrange Multiplier tests which showed that the Common Effect Model (CEM) was the best model. The results of the study show that partially liquidity does not have a significant effect on financial distress, even though it has a negative relationship direction. On the other hand, leverage has a positive and significant effect on financial distress, which indicates that increased debt use increases the risk of corporate financial difficulties. Simultaneously, liquidity and leverage have a significant effect on financial distress. These findings support the trade-off theory and signaling theory related to the risk of excessive use of debt.